Estudo de modelos semi-empíricos para a previsão de cobertura radio-elétrica em ambientes interiores - Vinicius de Araujo Lopes (2007)
The evolution of mobile telephony, the IEEE 802 LAN standard and others wireless communication systems have created a great demand for tools that provide support for planning theses systems. Many tools are about indoor enviroment. The objective of this work is to develop a software to make prediction of path loss atenuation in an indoor envirom,enviroment. This software is based on an semi-empirical model that had been improved with diffraction at doors and walls edges. In order to obtain the results, the user needs an image of the enviroment and create a file containing the coordinates of transmition and reception equipment position. It's also necessary to insert in this file the coordinates os walls and doors edges. If the user creates a grid of points representing reception position, it's possible to create an insoline graphic of predicted values. When compunting prediction of path loss, the user can choose between five different diffraction coefficient. The first is the coefficient for perfect conductors of Uniform Theory of Diffraction (UTD). The four remainders are heuristic coefficients developed by Luebbers, Holm, Aidi and Lavergnat, and one developed by Borges. The main goals of work is, at first, the comparison of path loss prediction using different diffraction coefficient, and than, the comparison of this results with a set of measurement. By this way, it's possible verifyng if program results are in agreement with the set of measurement. The results indicate that when using UTD coefficients for perfect conducting wedges, the attenuation prediction have always lesser values. The mean of these values are about 5 dB lesser than the attenuation values to Holm and Borges coefficients and about 2 dB lesser than Luebbers an Aidi coefficients.